Venetian humanism in the Mediterranean world: writing empire from the margins - Maglaque, E (2014)
My dissertation examines the cultural history of the Renaissance Venetian maritime empire. In this project I bring into conversation two historiographical subfields, the intellectual history of Venetian Renaissance humanism and the colonial history of the early modern Mediterranean, which have previously developed separately. In doing so, I examine the relationship between power and knowledge as it unfolded in the early modern Mediterranean. The ways in which Venetian Renaissance intellectual culture was shaped by its imperial engagements - and, conversely, how Venetian approaches to governance were inflected by humanist practices - are the central axes of my dissertation. In the first part of the dissertation, I examine the ways in which writing and textual collecting were used by elite Venetian readers to represent the geopolitical dimensions of their empire. I consider a group of manuscripts and printed books which contain technical, navigational, and cartographic writing and images about Venetian mercantile and imperial activity in the Mediterranean. In the second part, I undertake two case-studies of Venetian patrician governors who were trained in the humanist schools of Venice, before being posted to colonial offices in Dalmatia and the Aegean, respectively. I examine how their education in Venice as humanists influenced their experience and practice of governance in the stato da mar. Their personal texts offer an alternative intellectual history of empire, one which demonstrates the formation of political thought amongst the men actually practicing and experiencing imperial governance. Overall, I aim to build a picture of the ways in which literary culture, the physical world of the stato da mar, and political thought came to be entwined in the Venetian Renaissance; and then to describe how these dense relationships worked for the Venetian administrators who experienced them in the Mediterranean.